Evaluation of Virtual Learning-Based Early Childhood Character Education Management during the Covid-19 Period - Swantyka Ilham Prahesti; Sugiyo Pranoto; Amin Yusuf; Yuli Kurniawati Sugiyo Pranoto (International Conference on Science, Education, and Technology, 2021)
During the current pandemic, education in Indonesia is less focused. Students who do not understand the use of virtual applications and parents who are busy with their work make learning using virtual applications a very constraint. These obstacles are not only felt by students and parents, but also by educators. The purpose of this research is to find a solution to get the right learning model or method for educators, students, and parents during the current covid-19 pandemic. Qualitative Research Methods are the choice in evaluating character education learning at a time like this. This study focuses on planning, organizing, implementing, and evaluating systems in this study. The data taken using triangulation and data processing using descriptive analysis. Studies related to learning management, educators have not planned a learning system that supports student learning. In the implementation of learning, it is necessary to have a guidebook related to character education so that during the evaluation of learning there is an evaluation of the progress of the students. Thus, success in learning character education can be done repeatedly.